ANALISIS POLITIK HUKUM PERMENDIKBUD NOMOR 34 TAHUN 2018 DAN IMPLIKASINYA TERHADAP PENDIDIKAN VOKASI DI INDONESIA - Suwirza, Eka; Ismaidar; Sembiring, Tamaulina Br. (Yayasan Pendidikan Tanggui Baimbaian, 2024)
This study analyzes the legal political dimensions of the Regulation of the Minister of Education and Culture Number 34 of 2018 concerning National Standards for Vocational High School Education/Vocational Madrasah Aliyah. This study aims to uncover the political background, objectives, and implications of the regulation on the vocational education system in Indonesia. Through a qualitative approach, this study found that Permendikbud Number 34 of 2018 is a reflection of the government's efforts to improve the quality of human resources and the nation's competitiveness. This regulation also shows a paradigm shift in vocational education, where the business world and industry have a more central role. However, the implementation of this regulation still faces various challenges, both internally and externally. the implementation of this regulation still faces various challenges, such as the availability of facilities and infrastructure, the quality of teachers, and the dynamics of the world of work that continues to change. This study concludes that the success of the transformation of vocational education is highly dependent on the commitment and synergy between the government, the business world, and the community.